Clathrin regulates lymphocyte migration by driving actin accumulation at the cellular leading edge. Issue 10 (25th August 2016) - Ramírez‐Santiago, Guillermo; Robles‐Valero, Javier; Morlino, Giulia; Cruz‐Adalia, Aranzazu; Pérez‐Martínez, Manuel; Zaldivar, Airen; Torres‐Torresano, Mónica; Chichón, Francisco Javier; Sorrentino, Andrea; Pereiro, Eva; Carrascosa, José L.; Megías, Diego; et al.
Abstract : Clathrin drives local massive actin rearrangements observed at the leading edge of migrating lymphocytes, necessary for optimal cell polarization and lymphocyte migration. Clathrin populations involved in actin polymerization include clathrin associated to multivesicular bodies (MVBs), Golgi apparatus, and vesicles derived from plasma membrane. Abstract : Lymphocyte migration, which is essential for effective immune responses, belongs to the so‐called amoeboid migration. The lymphocyte migration is up to 100 times faster than between mesenchymal and epithelial cell types. Migrating lymphocytes are highly polarized in three well‐defined structural and functional zones: uropod, medial zone, and leading edge (LE). The actiomyosin‐dependent driving force moves forward the uropod, whereas massive actin rearrangements protruding the cell membrane are observed at the LE. These actin rearrangements resemble those observed at the immunological synapse driven by clathrin, a protein normally involved in endocytic processes. Here, we used cell lines as well as primary lymphocytes to demonstrate that clathrin and clathrin adaptors colocalize with actin at the LE of migrating lymphocytes, but not in other cellular zones that accumulate both clathrin and actin. Moreover, clathrin and clathrin adaptors, including Hrs, the clathrin adaptor for multivesicular bodies, drive local actin accumulation at the LE. Clathrin recruitment at the LE resulted necessary for a complete cell polarization and further lymphocyte migration in both 2D and 3D migration models. Therefore, clathrin, including the clathrin population associated to internal vesicles, controls lymphocyte migration by regulating actin rearrangements occurring at the LE.